2003
DOI: 10.1177/153537020322800107
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Conjugated Linoleic Acid Decreased Cachexia, Macrophage Tumor Necrosis Factor-α Production, and Modifies Splenocyte Cytokines Production1

Abstract: The effect of conjugated linoleic acid (CLA) on macrophage functions were studied in vitro, in vivo, and ex vivo. In RAW macrophage cell line, CLA (mixed isomers) was shown to inhibit lipopolysaccharide (LPS)-stimulated tumor necrosis factor-alpha (TNF-alpha) production. Two CLA isomers, c9,t11 and t10,c12, were tested on RAW cells and it was found that the c9,t11 was the isomer responsible for the inhibition of LPS-induced TNF-alpha production. BALB/c mice were used to determine the effect of dietary CLA on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
108
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(116 citation statements)
references
References 50 publications
5
108
2
1
Order By: Relevance
“…In the study of Kelley et al (2002) both the c9,t11-CLA and t10,c12-CLA significantly enhanced LPS-stimulated TNFa secretion in C57BL/6 mice, while Yamasaki et al (2003) reported a significant increase in Con A-induced TNFa production following dietary supplementation with the c9,t11-CLA alone. In contrast, in vitro studies with Raw264.7 macrophages showed that the c9,t11-CLA was associated with a dose-dependent decrease in LPS-induced TNFa production, with smaller decreases associated with the t10,c12-CLA isomer and a CLA isomeric mix (Yang & Cook, 2003). Recent human studies demonstrate that supplementation with CLA blends had no significant effect on ex vivo PHA-induced IL-2 secretion or LPS-stimulated TNFa production (Kelley et al, 2000(Kelley et al, , 2001Albers et al, 2003).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In the study of Kelley et al (2002) both the c9,t11-CLA and t10,c12-CLA significantly enhanced LPS-stimulated TNFa secretion in C57BL/6 mice, while Yamasaki et al (2003) reported a significant increase in Con A-induced TNFa production following dietary supplementation with the c9,t11-CLA alone. In contrast, in vitro studies with Raw264.7 macrophages showed that the c9,t11-CLA was associated with a dose-dependent decrease in LPS-induced TNFa production, with smaller decreases associated with the t10,c12-CLA isomer and a CLA isomeric mix (Yang & Cook, 2003). Recent human studies demonstrate that supplementation with CLA blends had no significant effect on ex vivo PHA-induced IL-2 secretion or LPS-stimulated TNFa production (Kelley et al, 2000(Kelley et al, , 2001Albers et al, 2003).…”
Section: Discussionmentioning
confidence: 96%
“…Three animal feeding trials showed that CLA isomeric blends significantly increased Con A-and PHA-induced IL-2 production in mice Hayek et al, 1999;Yang & Cook, 2003), whereas two studies reported no effect (Kelley et al, 2002;Yamasaki et al, 2003). Indeed, Kelley et al (2002) showed that feeding C57Bl/6N mice diets enriched with the purified c9,t11-CLA or t10,c12-CLA did not affect Con A-stimulated IL-2 production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…El consumo de lácteos estándar no permitiría alcanzar la ingestión diaria de CLA necesaria para la expresión de sus potenciales efectos preventivos de patologías cardiovasculares (Bhattacharya, et al, 2006), diabetes (Ryder, et al, 2001;Houseknecht, 1998), aterosclerosis (Lee, et al, 1994), cáncer (Ha, et al, 1990;Ip, et al, 1999), hipertensión (Bhattacharya, et al, 2006) y obesidad (Watkins y Li, 2003;Bhattacharya, et al, 2006). También se describen efectos antiinflamatorios del CLA (Yang y Cook, 2003;Miller, et al, 1994).…”
Section: Introductionunclassified